Jogos de tabuleiro: recurso lúdico na apropriação de leitura e escrita de crianças em situação de vulnerabilidade - Vasconcellos, Talita Silva Perussi (Universidade Federal de São Carlos, 2019)
The present research responds to the following question: Can the board game be considered as a resource in the reading and writing process? In order to answer this question, this study aimed to observe and analyze the use of board game in the process of appropriation of skills related to reading and writing of children in situations of social vulnerability. The present research was carried out in a Civil Society Organization, in the interior of the state of São Paulo. Fourteen girls, seven to ten years of age, who attended this organization participated in the study. The present qualitative research, characterized as participant research, used the procedures of observation, interview and pedagogical evaluation. It counted on three stages: 1. Initial sounding; 2. Intervention with board games; 3. Finalization. The results showed a gain in skills in the process of acquisition of reading and writing, since the application of the evaluations showed that all the girls advanced in the appropriation of writing abilities possibly by influence of the game. Therefore, it is possible to indicate that the board game can be considered as a facilitator in the process of appropriation of the abilities related to the reading and writing of children in situation of social vulnerability. It is also worth noting the importance of new studies that offer different mechanisms of teaching reading and writing skills, focusing on the potential and knowledge of the learner, so that, in fact, he becomes active in the teaching and learning process.
Board games: luddical resource in the approval of reading and writing of children in vulnerability situation
Keywords: Educação especial; Jogos de tabuleiro; Leitura e escrita; Vulnerabilidade social; Special education; Board games; Reading and writing; Social vulnerability; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO